Respostas cardiorrespiratórias do teleósteo de respiração aérea, Clarias gariepinus, exposto à hipóxia gradual - Belão, Thiago de Campos (2010)
Air-breathing fish are classified as obligatory (when breathing obligatory atmospheric air independently of the water O2 tension) or facultative air-breather (using an air breathing organ ABO -, when theirs gills are not able to extract all O2 necessary to maintain the aerobic mechanisms under hypoxic conditions). The catfish, Clarias gariepinus, is airbreathing fish that shows modifications on the gill lamella, forming a ventilatory fan, and on the 2o e 4o gill arches, forming an arborescent organ. These structures form the ABO of this specie.The objectives of the present study were: 1. To determine if C. gariepinus is an obligatory or a facultative air breather. 2. To analyze the cardio-respiratory responses ( VO2 - metabolic rate; VG - gill ventilation; VT ventilatory volume; fR respiratory frequency; EO2 O2 extraction from the ventilatory current; fH- heart frequency) in response to progressive hypoxia. 3. To verify if the critical O2 tension (PcO2) of this specie is correlated with the O2 uptake from the atmospheric air.To classify the air-breathing mode of C. Gariepinus, the fish (Wt ~ 350 g; n = 7) were maintained in normoxia during 24 hours without access to air. The fR maintained constant during all the experiment and there was no mortality, indicating that C. gariepinus is a facultative air-breather. To analyze the cardio-respiratory responses to progressive hypoxia, VO2 , EO2, fR, VT, VG , EO2 and fH were recorded under the following water O2 tensions(PwO2): 100, 70, 50 e 30 mmHg. Fish maintained a constant VO2 until the PcO2 (~ 55 mmHg), below which VO2 decreased significantly. This decreasing was followed with the significant reduction of EO2 in PinspO2 of 62,7 ± 1,30 mmHg reaching values of 19,6 ± 1,9 % in severe hypoxia. The VG and the VT increased progressively until PinspO2 of 28,0 ± 0,5 mmHg, reaching highest values of, respectively, 1545,7 ± 63,5 mLH2O.kg-1.min-1, 33,9 ± 0,8 mLH2O.Kg-1.resp-1 e 57,2 ± 1,4 resp.min-1. The fH reduced progressively from 43,4 ± 0,4 bpm, in normóxia, arriving significant values just above the PcO2 and reaching minimum values (19,2 ± 3,0 bpm) in severe hypoxia. Under progressive hypoxia (100, 70, 50, 30 e 20 mmHg) and with the access to the atmospheric air, C. gariepinus (Wt ~ 610 g; n = 9) presented a 5-fold increase in the air-breathing frequency (fRA). A bradycardia was observed just before the air breath and a tachycardia just after.Concluding, C. gariepinus is a continuous facultative air-breathing fish that regulate the 2 O V until the PcO2 of ~54 mmHg. Below this tension fish increase the VG mainly due to a larger increase of VT (lower metabolic cost of VG ). The hypoxic pre-air breath bradycardia is characteristic of aquatic breathers while the post-air breath tachycardia is typical of air respirators. The fRA increased proportionally with the progressive hypoxia, mainly just above the PcO2. These results show that C. gariepinus is adapted to survive at hypoxic habitats and that this species show a higher dependence of the atmospheric air than the others facultative air-breathing fishes.